Relationship between Local Television News Agenda and Public Agenda on Development Issues in Southeast Sulawesi Province - Zulfiah Larisu; Nunung Prajarto; Subejo Subejo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study examines the relationship of local television news agenda in Southeast Sulawesi with a public agenda related to issues of development and test variables or factors that strengthen the relationship between the media agenda to the public agenda in the Southeast. This research is a kind of explanation to the agenda that analyze media content analysis and public agenda with the survey method. This research was conducted in TVRI Stasiun Sulawesi Tenggara and Southeast Sulawesi provincial public with a population of about 1866 TVRI Stasiun Sulawesi Tenggara news items, and the public population as much as 260.867 persons. Samples totaling 584 items of news media and the public sample totaled 65 respondents taken by purposive sampling. Collecting data using the media agenda coding sheet and variables influence the public agenda using a questionnaire with data analysis using statistical test of correlation. Statistical test results Nonparametric Spearman Rho's models showed that TVRI Stasiun Sulawesi Tenggara agenda not significantly associated with a public agenda Southeast Sulawesi Province. Variables that influence is the level of use and the level of media interest in the issue. A high level of media usage, affect the relationship between the media agenda and the public agenda in the 0.05 at 0883 values (p> 0.05), as well as a high level of interest issues, affect the relationship between the media agenda and the public agenda at the 0.05 significance with a value of 0857 (p > 0.05). Thus the need to improve pemberitakan issues that interest and needs of the public so that the public can increase the use of the media by the public so as to enhance the relationship between the media agenda and the public agenda.